Effect of heat acclimation when existing training load remains constant - a pilot study within international triathletes - Lee, C. W. D.; James, C. A.; Li, P. Y. C.; So, C. H. R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The acute nature of the induction and decay of heat acclimation (HA) adaptations often necessitates that HA is conducted in the weeks immediately preceding a competition, potentially interfering with a planned training taper. Therefore, we investigated the effect of a mixed active and passive heat acclimation protocol, during the 3 weeks prior to the 2022 U23 Triathlon World Championships, when the planned external training load was maintained.